2011
DOI: 10.17221/57/2011-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Flower thinning of apple cultivar Braeburn using ammonium and potassium thiosulfate: Short communication

Abstract: Milić B., Magazin N., Keserović Z., Dorić M., 2011. Flower thinning of apple cultivar Braeburn using ammonium and potassium thiosulfate -Short communicaton. Hort. Sci. (Prague), 38: 120-124.Ammonium and potassium thiosulfate are used commercially or experimentally as flower thinners because they are considered user, environment and consumer safe. The thinning trials were conducted in 2009 and 2010, on three-and four-year-old Braeburn Mariri Red* trees. The chemicals were applied at 1%, 2% and 3% rates of ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…A negative linear relationship exists between fruit weight and diameter on the one hand and fruit to leaf area ratio on the other (Whiting, Lang 2004), which is why a healthy leaf area is a crucial factor that affects fruit size. It is previously reported by Milić et al (2011) that phytotoxicity occurred on apple leaves after 3% ATS application and caused a decrease in fruit weight. It is assumed that more leaf damage occurred on apple than on sweet cherry because, at the time of flowering, an apple tree develops a larger leaf area susceptible to burning than sweet cherry.…”
Section: Effects Of Thinning On Fruit Qualitymentioning
confidence: 93%
See 1 more Smart Citation
“…A negative linear relationship exists between fruit weight and diameter on the one hand and fruit to leaf area ratio on the other (Whiting, Lang 2004), which is why a healthy leaf area is a crucial factor that affects fruit size. It is previously reported by Milić et al (2011) that phytotoxicity occurred on apple leaves after 3% ATS application and caused a decrease in fruit weight. It is assumed that more leaf damage occurred on apple than on sweet cherry because, at the time of flowering, an apple tree develops a larger leaf area susceptible to burning than sweet cherry.…”
Section: Effects Of Thinning On Fruit Qualitymentioning
confidence: 93%
“…Although ammonium thiosulfate (ATS) successfully thins apple (Milić et al 2011) and peach flowers (Coneva, Cline 2006), its application on cherries, although effective in reducing fruit set, did not improve fruit size, weight and soluble solids contents (Schoedl et al 2009). Surfactant Armothin (Southwick et al 1996) and Tergitol-TMN-6 (Ambrožič Turk et al 2014) showed a promising flower thinning efficacy in peach while Silwet 408 significantly reduced fruit set in peach (Baugher et al 2008) and apple (Bound, Klein 2010).…”
mentioning
confidence: 99%
“…At 1.5%, ATS shows a strong thinning which is capable of decreasing half of the amount of flowers produced by European plums, reducing yield and fruit set more severely than hand thinning, and as a consequence, increasing the fruit weight and quality (Meland, 2007). On apple, ATS at 2% significantly reduced fruit set and increased fruit weight (Milić et al, 2011). In the United States and Europe, the use of ATS is consolidated and there are plenty of research on this theme.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of effective options other than hormonal thinners are still one of the main discussions among apple producers. There is plenty of information about the potential use of ATS as a chemical blossom thinner in cropping systems around the world (Meland, 2007;Milić et al, 2011;Maas, 2016), and it may have potentially promising results in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Braeburn as it produces flowers abundantly and has a high fruit set as well. Since, high crop load leads in decreasing fruit size especially in young apple trees (Milić et al, 2011).…”
Section: Introductionmentioning
confidence: 99%